Dominant Role of Meridional Circulation in Regulating the Anomalous Subsidence of the Western Pacific Subtropical High in Early Summer 2020 - Zhao, Yuheng; Cheng, Jianbo; Feng, Guolin; Zheng, Zhihai; Zhi, Rong; Zhang, Zengping; Yan, Jinlong; Zuo, Dongdong (Frontiers in Physics, 2022)
Anomalous subsidence over the western part of the western Pacific subtropical high (WPSH) caused record-breaking precipitation anomalies over the Yangtze-Huaihe River catchment in early summer 2020 (June–July 2020). The meridional circulation (MC) made a positive contribution to this anomalous subsidence, while the zonal circulation (ZC) made a negative contribution. The quantitative contributions of the MC and ZC to this anomalous subsidence were approximately 110% and –10% in June, 130% and –30% in July, and 120% and –20% for the mean of June and July, respectively, suggesting that the MC played a dominant role in the anomalous subsidence of the western part of the WPSH. The anomalous MC, with a rising branch located at the Maritime Continent and a descending branch located over South China, was forced by the warming of the northern tropical Indian Ocean and the rapidly developed La Niña event, which further resulted in the intensification and southwestward expansion of the WPSH and thus in heavy rainfall over the Yangtze River region.